The Influence of Instagram-Based Electronic Word of Mouth (E-WOM) on Tourists' Visiting Decisions to Malioboro Street, Yogyakarta - Ningsi, Devie Purnama; Yovita, Vanesha (Journal of Tourism Sustainability, 2025)
Malioboro Street is a renowned tourist destination in Yogyakarta, Indonesia, frequently visited by domestic and international travellers. In the digital transformation era, destinations have increasingly utilised digital platforms, particularly Instagram, to attract visitors through Electronic Word of Mouth (e-WOM). This study partially and simultaneously examines the influence of three dimensions of e-WOM—Intensity, Valence of Opinion, and Content—on tourists' visiting decisions. Employing a quantitative research method incorporating multiple linear regression and descriptive statistical analysis, the findings indicate that Intensity does not significantly influence visiting decisions, while Valence of Opinion and Content have significant partial effects. Simultaneously, all three dimensions collectively influence tourists' visiting decisions with a coefficient of determination (R²) of 60.1%, indicating substantial influence. The results highlight the strategic importance of managing e-WOM on Instagram to support sustainable tourism development for Malioboro Street.